KONSEP EVALUASI PEMBELAJARAN BAHASA ARAB - Nurzahira, Fadhilah; Jayadi, M. Irwan; Ridlo, Ubaid (Universitas Islam Negeri Sumatera Utara Medan, 2025)
An essential component of the educational system, learning evaluation measures the success of the teaching and learning process as well as the attainment of learning objectives. Evaluation plays a strategic role in Arabic language learning because it covers the four primary language skills-istima‘ (listening), kalam (speaking), qira‘ah (reading), and kitabah (writing)-in addition to evaluating mastery of cognitive components like mufradat (vocabulary) and qawa‘id (grammar). In addition to explaining the goals, purposes, and forms of evaluation pertinent to Arabic language instruction, this article attempts to theoretically investigate the ideas of evaluation, assessment, and measurement in the context of learning the language.The study's findings demonstrate the need for a thorough assessment of Arabic language acquisition that takes into account the cognitive, emotional, and psychomotor domains and makes use of a variety of tools in order to characterize students' overall communicative proficiency.